Distress of an industrial building constructed on an expansive soil: a case study from India. Issue 3 (13th July 2018) - Kumar, T Ashok; Robinson, R G; Thyagaraj, T
Abstract : This paper presents a case study of a two-storey building in Oragadam, near Chennai (India), which has undergone distress due to the presence of expansive soil. Undulations in the floors, cracks in partition walls and non-uniform heave in the pavement are some of the failure patterns noticed in and around the structure. Undisturbed soil samples were collected from the site to identify the cause of distress. From the field inspection and laboratory testing it was found that the use of unsuitable fill material (expansive soil) followed by the ingress of excess water from the garden and improper planning of the location of the rainwater-harvesting system were the causes of the initiation of distress in the building.